High-strength and plastic rare earth treated composite structure wear-resistant steel and production method thereof

By adjusting element components and process design, high-strength plastic rare earth treatment composite-phase structure wear-resistant steel is prepared, which solves the problems of prone to cracking and high cost in harsh environments, and realizes the development of low-cost, high-performance wear-resistant steel.

CN117867399BActive Publication Date: 2025-03-21HUNAN VALIN LIANYUAN IRON & STEEL CO LTD

Patent Information

Application Number
CN202311812963.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-26
Publication Date
2025-03-21
Estimated Expiration
2043-12-26

AI Technical Summary

Technical Problem

Existing wear-resistant steels are prone to cracking in harsh service environments, and high-performance wear-resistant steels are costly, which poses technical challenges in how to develop low-cost, high-performance wear-resistant steels.

Method used

By adjusting the element components and contents of the wear-resistant steel with high-strength plastic rare earth treatment complex structure, low-carbon and alloying components are designed, combined with rare earth Ce treatment, recrystallization zone and non-recrystallization zone rolling, online quenching and tempering processes, wear-resistant steel with martensite, bainite, residual austenite and nano-precipitated refractory phase structure are prepared.

Benefits of technology

High strength, excellent plasticity, wear resistance and bending performance are achieved, while reducing the production cost of wear-resistant steel and avoiding the disadvantages of adding precious alloy elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117867399B_ABST
    Figure CN117867399B_ABST
Patent Text Reader

Abstract

The present application provides a high-strength and plastic rare earth treated multi-phase wear-resistant steel and a production method thereof. The high-strength and plastic rare earth treated multi-phase wear-resistant steel comprises the following components in percentage by mass: C: 0.10-0.30wt%; Si: 0.30-1.5wt%; Mn: 1.0-3.5wt%; Mo: 0.10-0.50wt%; Nb: 0.01-0.05%; Ti: 0.01-0.10wt%; Al: 0.030-0.070wt%; Ce: 0.01-0.05wt%; P≤0.008wt%; S≤0.005wt%; B: 0.0010-0.0050wt%; O≤0.0020%; N≤0.0020%, and the balance is Fe. The present application manufactures high-strength and plastic rare earth treated multi-phase wear-resistant steel with excellent plasticity, wear resistance and bending performance by adjusting the element components and their contents in the high-strength and plastic rare earth treated multi-phase wear-resistant steel. In addition, the wear-resistant steel in the embodiment of the present application does not add precious alloy elements such as Ni, Cr, and Mo, thereby reducing the production cost of the wear-resistant steel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of alloy wear-resistant steel, and in particular to a high-strength and plastic rare earth treated complex phase structure wear-resistant steel and a production method thereof. Background Art

[0002] Wear-resistant steel is widely used in many industries such as metallurgy, railways, military and electricity, and has become one of the indispensable key materials. According to relevant statistics, the economic losses caused by wear of mechanical equipment and its parts account for about 4% of the total national economic output value. In the face of increasingly severe resource, energy and environmental problems in the world, the development and application of wear-resistant steel materials have received great attention at home and abroad.

[0003] The wear resistance of steel is not only related to strength and hardness, but also to its toughness. High manganese steel is a single austenite structure with low hardness. It is mainly used in high stress environments. Austenite is used to induce martensite phase transformation to improve wear resistance. In medium and low stress environments, austenite cannot fully induce martensite phase transformation, so wear resistance cannot be guaranteed. The currently widely used martensitic low-alloy wear-resistant steel has high strength and hardness, but poor plasticity and toughness, and is prone to cracking in harsh service environments.

[0004] The wear-resistant steel with a dual-phase structure of martensite plus austenite plus nano-precipitation phase or martensite plus bainite plus retained austenite plus nano-precipitation phase uses the retained austenite to induce martensitic transformation (Transformation Induced Plasticity, TRIP effect) to improve the strength and toughness of the steel, and the precipitation strengthening effect of the nano-precipitation phase, etc., so that the dual-phase structure wear-resistant steel has excellent strength and plastic toughness, bending performance and wear resistance. However, the cost of high-performance wear-resistant steel in the existing technology is relatively high. It is the development direction of domestic wear-resistant steel to explore low-cost high-performance wear-resistant steel from the perspective of overall design and process flow.

[0005] Patent CN 108004469 B describes a low alloy high toughness QPT wear-resistant steel plate and its preparation method. The composition design is to add alloy elements such as Cr, Mo, Ni, Cu, and adopt a quenching-partitioning-tempering process to obtain a martensite plus bainite plus residual austenite structure to obtain a high strength and toughness wear-resistant steel. The alloy design contains precious metals such as Cr, Mo, Ni, and the quenching-partitioning-tempering process is complicated. Summary of the invention

[0006] The embodiment of the present application provides a high-strength and plastic rare earth treated multiphase structure wear-resistant steel and a production method thereof. The wear-resistant steel structure is a multiphase structure of martensite, austenite and nano-precipitate phase or a multiphase structure of martensite, bainite, residual austenite and nano-precipitate phase, and has excellent wear resistance.

[0007] In the first aspect, an embodiment of the present application provides a high-strength and plastic rare earth-treated complex phase wear-resistant steel, comprising the following components in percentage by mass: C: 0.10-0.30wt%; Si: 0.30-1.5wt%; Mn: 1.0-3.5wt%; Mo: 0.10-0.50wt%; Nb: 0.01-0.05%; Ti: 0.01-0.10wt%; Al: 0.030-0.070wt%; Ce: 0.01-0.05wt%; P≤0.008wt%; S≤0.005wt%; B: 0.0010-0.0050wt%; O≤0.0020%; N≤0.0020%, and the balance is Fe.

[0008] According to the embodiment of the first aspect of the present application, the metallographic structure of the high-strength and plastic rare earth treated complex phase wear-resistant steel is a complex phase structure, and the complex phase structure includes martensite, bainite, retained austenite and nano-precipitation phase.

[0009] According to the embodiment of the first aspect of the present application, the metallographic structure of the high-strength and plastic rare earth treated complex phase wear-resistant steel includes, by volume percentage, 50% to 70% martensite, 26% to 46% bainite, 2% to 10% residual austenite and 0.5% to 2.0% nano-precipitate phase.

[0010] According to the embodiment of the first aspect of the present application, the Brinell hardness of the high-strength and plastic rare earth treated multiphase wear-resistant steel is 440HB-480HB, the yield strength is greater than 1300MPa, and the elongation is ≥15.0%.

[0011] In a second aspect, the present application provides a method for producing high-strength and plastic rare earth treated multi-phase wear-resistant steel, which is used to produce the high-strength and plastic rare earth treated multi-phase wear-resistant steel, comprising:

[0012] The molten steel is cast to obtain a casting billet, which includes the following components in percentage by weight: C: 0.10-0.30wt%; Si: 0.30-1.5wt%; Mn: 1.0-3.5wt%; Mo: 0.10-0.50wt%; Nb: 0.01-0.05wt%; Ti: 0.01-0.10wt%; Al: 0.030-0.070wt%; Ce: 0.01-0.05wt%; P≤0.008wt%; S≤0.005wt%; B: 0.0010-0.0050wt%; O≤0.0020%; N≤0.0020%, and the balance is Fe;

[0013] The ingot is heated in a heating furnace, subjected to controlled rolling, directly quenched and tempered online to obtain high-strength and plastic rare earth treated complex phase structure wear-resistant steel.

[0014] According to an embodiment of the second aspect of the present application, in the step of casting molten steel to obtain a cast ingot, the casting temperature is 1500°C to 1530°C.

[0015] According to an embodiment of the second aspect of the present application, in the heating step, the ingot is placed in a heating furnace for homogenization, and the heating temperature is 1150-1200°C.

[0016] According to an embodiment of the second aspect of the present application, in the controlled rolling step, the ingot is rolled in the recrystallization zone at 1050-1120°C and in the non-recrystallization zone at 880-950°C, and after rolling, it is rapidly cooled to 400-500°C and air-cooled.

[0017] According to an embodiment of the second aspect of the present application, in the controlled rolling step, the reduction amount per rolling pass is 20-30%, and the cumulative reduction rate is 50%.

[0018] According to an embodiment of the second aspect of the present application, in the tempering step, the tempering temperature is 190-360°C.

[0019] Compared with the prior art, this application has at least the following beneficial effects:

[0020] The present application manufactures high-strength-plastic rare earth-treated multiphase wear-resistant steel with excellent strength-plasticity, wear resistance and bending performance by adjusting the element components and their contents in the high-strength-plastic rare earth-treated multiphase wear-resistant steel. In addition, the wear-resistant steel in the embodiment of the present application does not add precious alloy elements such as Ni, Cr, and Mo, thereby reducing the production cost of the wear-resistant steel. The addition of rare earth cerium greatly reduces the oxygen, sulfur, and nitrogen content in the steel, thereby controlling the number and size of inclusions. Strong carburization forming elements niobium and titanium are conducive to grain refinement and precipitation strengthening. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The features, advantages and technical effects of exemplary embodiments of the present application will be described below with reference to the accompanying drawings.

[0022] Figure 1 This is a microstructure diagram of the high-strength and plastic rare earth treated complex phase wear-resistant steel of Example 1 of the present application after hot rolling and tempering at 200°C;

[0023] Figure 2 This is the room temperature stress-strain curve of the high-strength and plastic rare earth treated complex phase wear-resistant steel of Example 1 of the present application after hot rolling and tempering at 200°C. DETAILED DESCRIPTION

[0024] The following detailed description and drawings of the embodiments of the present application are used to illustrate the principles of the present application, but cannot be used to limit the scope of the present application, that is, the present application is not limited to the described embodiments.

[0025] In the description of the present application, it should be noted that, unless otherwise specified, "multiple" means more than two; the terms "upper", "lower", "left", "right", "inside", "outside", etc., indicating the orientation or positional relationship are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. In addition, the terms "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance. "Vertical" does not require verticality in the strict sense, but may include allowable errors. "Parallel" does not require parallelism in the strict sense, but may include allowable errors.

[0026] Whether the retained austenite in the complex phase wear-resistant steel can produce the TRIP effect is related to its stability. Factors affecting the stability of the retained austenite include carbon and alloying elements, grain size, etc. Domestic and foreign scholars have regulated the stability of the retained austenite by adding alloying elements such as chromium, nickel, and molybdenum and quenching and partitioning methods. The cost increases due to the addition of precious alloying elements, and the quenching and partitioning process is complex and the process is long. Under the severe situation caused by many factors such as the rise in raw materials, from the perspective of saving resources and energy and reducing costs, developing wear-resistant steel materials that use less precious elements such as chromium, molybdenum, and nickel, and exploring low-cost, high-performance wear-resistant steel from the perspective of comprehensive design and process flow is the development direction of domestic wear-resistant steel.

[0027] In view of this, the inventors of the present application, after a large number of experimental studies, provide high-strength and plastic rare earth treated complex phase structure wear-resistant steel and a production method thereof, aiming to improve its plasticity, wear resistance and bending performance, and reduce costs.

[0028] High strength and plasticity rare earth treated composite structure wear-resistant steel

[0029] In the first aspect, an embodiment of the present application provides a high-strength and plastic rare earth-treated complex phase wear-resistant steel, comprising the following components in percentage by mass: C: 0.10-0.30wt%; Si: 0.30-1.5wt%; Mn: 1.0-3.5wt%; Mo: 0.10-0.50wt%; Nb: 0.01-0.05%; Ti: 0.01-0.10wt%; Al: 0.030-0.070wt%; Ce: 0.01-0.05wt%; P≤0.008wt%; S≤0.005wt%; B: 0.0010-0.0050wt%; O≤0.0020%; N≤0.0020%, and the balance is Fe.

[0030] The present application manufactures high-strength-plastic rare earth-treated multiphase wear-resistant steel with excellent strength-plasticity, wear resistance and bending performance by adjusting the element components and their contents in the high-strength-plastic rare earth-treated multiphase wear-resistant steel. In addition, the wear-resistant steel in the embodiment of the present application does not add precious alloy elements such as Ni, Cr, and Mo, thereby reducing the production cost of the wear-resistant steel. The addition of rare earth cerium greatly reduces the oxygen, sulfur, and nitrogen content in the steel, thereby controlling the number and size of inclusions. Strong carburization forming elements niobium and titanium are conducive to grain refinement and precipitation strengthening.

[0031] Next, the role of each chemical component of high-strength and plastic rare earth treated complex phase wear-resistant steel is described in detail:

[0032] Carbon: Solid solution strengthening and precipitation of second phase particles can improve the strength and hardness of steel, and solid solution in austenite increases the stability of austenite. When the carbon content in steel is greater than 0.30wt%, twin martensite is obtained by quenching, which reduces the toughness of the steel. High carbon content is not good for welding performance, so the carbon content is designed to be 0.10-0.30wt% in this application. Exemplarily, the carbon content is 0.10wt%, 0.12wt%, 0.14wt%, 0.16wt%, 0.18wt%, 0.20wt%, 0.22wt%, 0.24wt%, 0.26wt%, 0.28wt%, 0.30wt% or a range consisting of any two of the above values.

[0033] Silicon: The main function of silicon in steel is deoxidation. The strength is improved by the solid solution strengthening effect of silicon. Silicon can inhibit the precipitation of cementite during tempering. However, if the silicon content is too high, FeSiO4 oxide is easily formed on the hot-rolled surface, which increases the difficulty of deoxidation. Therefore, the silicon content is designed to be Si: 0.3-3.5wt% in this application. Exemplarily, the silicon content is 0.3wt%, 0.4wt%, 0.5wt%, 0.5wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2.0wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3.0wt%, 3.1wt%, 3.2wt%, 3.3wt%, 3.4wt%, 3.5wt% or a range consisting of any two of the above values.

[0034] Manganese: Manganese improves the hardness and strength of wear-resistant steel, strongly increases hardenability, and is easy to obtain martensite structure after quenching, and increases the amount of residual austenite. However, manganese is an element that is sensitive to overheating. If the heating temperature is too high during quenching, it will cause coarse grains; manganese has a large segregation coefficient during solidification, and it is easy to segregate at the grain boundary, which has an adverse effect on quenching performance. Therefore, the manganese content is designed to be 1.0-3.50wt% in this application. Illustratively, the manganese content is 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2.0wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3.0wt%, 3.1wt%, 3.2wt%, 3.3wt%, 3.4wt%, 3.5wt% or a range consisting of any two of the above values.

[0035] Molybdenum: Molybdenum improves the hardenability of wear-resistant steel. Molybdenum forms (Mo, Ti, Nb) C, N composite precipitation phase with (Ti, Nb) C, N carbonitride, reduces the growth rate of carbonitride, obtains nano-sized precipitation phase, and is beneficial to improve strength. Therefore, the molybdenum content in this application is designed to be 0.10-0.50wt%. Exemplarily, the molybdenum content is 0.10wt%, 0.12wt%, 0.14wt%, 0.16wt%, 0.18wt%, 0.20wt%, 0.22wt%, 0.24wt%, 0.26wt%, 0.28wt%, 0.30wt%, 0.32wt%, 0.34wt%, 0.36wt%, 0.38wt%, 0.40wt%, 0.42wt%, 0.44wt%, 0.46wt%, 0.48wt%, 0.50wt% or a range consisting of any two of the above values.

[0036] Niobium: Niobium is a strong carbonitride-forming element, which inhibits the growth of austenite grains, increases the recrystallization temperature of steel during rolling, inhibits austenite recrystallization, and refines grains; niobium precipitates in ferrite, improves the strength of steel, and prevents the coarsening of grains in the heat-affected zone during welding. Therefore, the niobium content is designed to be 0.01-0.05wt% in this application. For example, the niobium content is 0.01wt%, 0.015wt%, 0.02wt%, 0.025wt%, 0.03wt%, 0.035wt%, 0.04wt%, 0.045wt%, 0.05wt%, or a range consisting of any two of the above values.

[0037] Titanium: Titanium has a strong affinity with carbon, nitrogen and sulfur. Titanium and carbon and nitrogen form titanium carbonitride, which can refine grains and strengthen precipitation. Titanium and sulfur react to form titanium sulfide, which has a much lower plasticity than manganese sulfide, thereby reducing the harmful effects of manganese sulfide and improving lateral performance. w(Ti(effective titanium))=w(Ti(total))-3.4w(N)-3w(S)-w(TiC(strain induced precipitation)). Therefore, the titanium content is designed to be 0.01-0.10wt% in this application. For example, the titanium content is 0.01wt%, 0.02wt%, 0.03wt%, 0.04wt%, 0.05wt%, 0.06wt%, 0.07wt%, 0.08wt%, 0.09wt%, 0.10wt% or a range consisting of any two of the above values.

[0038] Aluminum: The main function of adding aluminum to steel is deoxidation and adjusting the grain size. Aluminum combines with nitrogen to form AlN to eliminate the adverse effects of nitrogen on steel performance, improve impact energy, and refine grains. Therefore, the aluminum content is designed to be 0.02-0.04wt% in this application. Exemplarily, the aluminum content is 0.020wt%, 0.024wt%, 0.026wt%, 0.028wt%, 0.030wt%, 0.032wt%, 0.034wt%, 0.036wt%, 0.038wt%, 0.04wt% or a range consisting of any two of the above values.

[0039] Cerium: Rare earth cerium segregates at the grain boundary, which can inhibit the grain boundary segregation of harmful elements such as phosphorus, sulfur, and tin, and play a role in purifying the grain boundary. In addition, cerium segregates at the grain boundary to change the grain boundary energy and structure, reduce the interface energy, and reduce the driving force for grain growth, thereby inhibiting the growth of austenite grains, refining austenite grains, and making martensite laths finer. Rare earth cerium inclusions can serve as foreign crystal nuclei for the initial austenite inhomogeneous nucleation. Therefore, the design amount of Ce element in this application is less than 0.05wt%. Exemplarily, the cerium content is 0.01wt%, 0.015wt%, 0.02wt%, 0.025wt%, 0.03wt%, 0.035wt%, 0.04wt%, 0.045wt%, 0.05wt% or a range consisting of any two of the above values.

[0040] Phosphorus: The increase of phosphorus content in steel increases the ductile-brittle transition temperature of steel. During the tempering process, phosphorus grain boundaries in steel segregate, causing cold brittleness of steel. Therefore, the P content is less than 0.008wt%. Exemplarily, the phosphorus content is 0.001wt%, 0.002wt%, 0.003wt%, 0.004wt%, 0.005wt%, 0.006wt%, 0.007wt%, 0.008wt% or a range consisting of any two of the above values.

[0041] Sulfur: Sulfur is easy to form MnS inclusions with Mn, which is not good for toughness. It forms (FeS+Fe) low melting point eutectic structure at high temperature, causing hot brittleness. Therefore, the content of sulfur element is less than 0.005wt%. Exemplarily, the content of sulfur element is 0.001wt%, 0.002wt%, 0.003wt%, 0.004wt%, 0.005wt% or a range consisting of any two of the above values.

[0042] Oxygen: Oxygen is easy to form oxide inclusions such as Al2O3, MnO, SiO2 with Al, Mn, Si, etc., which is not good for the plasticity and toughness of steel. Therefore, the content of O is less than 0.0020wt%. Exemplarily, the content of oxygen is 0.0005wt%, 0.0010wt%, 0.0015wt%, 0.0020wt% or a range consisting of any two of the above values.

[0043] Nitrogen: N forms AlN with Al to weaken or eliminate the aging phenomenon, so the N content is less than 0.0020 wt %. Exemplarily, the nitrogen content is 0.0005 wt %, 0.0010 wt %, 0.0015 wt %, 0.0020 wt % or a range consisting of any two of the above values.

[0044] In summary, the present application adjusts the elemental components and their contents in the high-strength and plastic rare earth treated complex phase structure wear-resistant steel, and the chemical components work together to produce high-strength and plastic rare earth treated complex phase structure wear-resistant steel with excellent plasticity, wear resistance and bending performance, and reduces the production cost of wear-resistant steel. The high-strength and plastic rare earth treated complex phase structure wear-resistant steel provided by the present application can be used in many industries such as metallurgy, railways, military and electric power.

[0045] In some embodiments, the metallographic structure of the high-strength and ductile rare earth treated complex phase wear-resistant steel is a complex phase structure, and the complex phase structure includes martensite, bainite, retained austenite and nano-precipitated phase.

[0046] The high-strength and plastic rare earth treated complex phase wear-resistant steel provided in the embodiment of the present application has a complex phase structure, wherein the complex phase wear-resistant steel is martensite plus austenite plus nano-precipitation phase or martensite plus bainite plus residual austenite plus nano-precipitation phase. The retained austenite is used to induce martensitic phase transformation (Transformation Induced Plasticity, TRIP effect) to improve the strength and toughness of the steel, the precipitation strengthening effect of the nano-precipitation phase, etc., so that the complex phase wear-resistant steel has excellent strength and plastic toughness, bending performance and wear resistance.

[0047] In some embodiments, the metallographic structure of the high-strength and ductile rare earth treated multiphase wear-resistant steel includes, by volume percentage, 50% to 70% martensite, 26% to 46% bainite, 2% to 10% retained austenite and 0.5% to 2.0% nano-precipitates.

[0048] Exemplarily, in terms of volume percentage, the content of martensite in the metallographic structure of the high-strength and ductile rare earth treated complex phase wear-resistant steel is 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70% or a range consisting of any two of the above values.

[0049] Exemplarily, in volume percentage, the content of bainite in the metallographic structure of the high-strength and ductile rare earth treated complex phase wear-resistant steel is 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46% or a range consisting of any two of the above values.

[0050] Exemplarily, in volume percentage, the content of retained austenite in the metallographic structure of the high-strength and ductile rare earth treated complex phase wear-resistant steel is 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two of the above values.

[0051] Exemplarily, in volume percentage, the content of nano-precipitated phase in the metallographic structure of the high-strength and ductile rare earth treated complex phase wear-resistant steel is 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0% or a range consisting of any two of the above values.

[0052] In some embodiments, the high-strength and plastic rare earth treated multi-phase wear-resistant steel has a Brinell hardness of 440HB to 480HB, a yield strength of greater than 1300 MPa, and an elongation of ≥15.0%.

[0053] Production method of high-strength and plastic rare earth treated composite structure wear-resistant steel

[0054] In a second aspect, the present application provides a method for producing high-strength and plastic rare earth treated multi-phase wear-resistant steel, which is used to produce the high-strength and plastic rare earth treated multi-phase wear-resistant steel, comprising:

[0055] The molten steel is cast to obtain a casting billet, which includes the following components in percentage by weight: C: 0.10-0.30wt%; Si: 0.30-1.5wt%; Mn: 1.0-3.5wt%; Mo: 0.10-0.50wt%; Nb: 0.01-0.05wt%; Ti: 0.01-0.10wt%; Al: 0.030-0.070wt%; Ce: 0.01-0.05wt%; P≤0.008wt%; S≤0.005wt%; B: 0.0010-0.0050wt%; O≤0.0020%; N≤0.0020%, and the balance is Fe;

[0056] The ingot is heated in a heating furnace, subjected to controlled rolling, directly quenched and tempered online to obtain high-strength and plastic rare earth treated complex phase structure wear-resistant steel.

[0057] In some embodiments, the production method also includes molten steel smelting, RH, and LF-VD treatment to control the content of impurity elements such as sulfur, phosphorus, oxygen, and arsenic.

[0058] The present application adjusts the element components and their contents in the high-strength and plastic rare earth treated complex phase wear-resistant steel, adopts low carbon and alloying component design, and controls the contents of impurity elements such as sulfur, phosphorus, oxygen, and arsenic through the mutual cooperation of carbon, silicon, manganese, molybdenum, niobium, titanium, etc., and is supplemented by rare earth Ce treatment, RH, and LF-VD treatment. The recrystallization zone controlled rolling and non-recrystallization zone controlled rolling, controlled cooling rate, and online quenching and tempering processes are adopted to obtain a structure of martensite + austenite + nano-precipitation phase complex phase structure or rolled martensite plus bainite plus residual austenite plus nano-precipitation phase complex phase structure, and manufactures high-strength and plastic rare earth treated complex phase wear-resistant steel with excellent strong plasticity, wear resistance and bending performance. In addition, the wear-resistant steel in the embodiment of the present application does not add precious alloy elements such as Ni, Cr, and Mo, thereby reducing the production cost of the wear-resistant steel. Adding rare earth cerium greatly reduces the oxygen, sulfur and nitrogen content in steel, thereby controlling the number and size of inclusions. Strong carburization of niobium and titanium elements is beneficial to grain refinement and precipitation strengthening. Controlled rolling and cooling processes are used to refine grains and control nano-precipitation phases, thereby improving the toughness and wear resistance of steel.

[0059] In addition, the embodiment of the present application adopts controlled rolling, controlled cooling and online quenching technology, and the hot-rolled plate is directly tempered, which greatly shortens the process flow.

[0060] In some embodiments, in the step of casting molten steel to obtain a casting ingot, the casting temperature is 1500°C to 1530°C.

[0061] The casting temperature is 1500℃~1530℃, which can avoid the formation of coarse solidification structure and defects.

[0062] In some embodiments, in the heating step, the ingot is placed in a heating furnace for homogenization, and the heating temperature is 1150-1200°C.

[0063] The heating temperature of the ingot is 1150-1200°C, which can make the structure uniform. Preferably, the holding time is calculated as 1 min / mm.

[0064] In some embodiments, in the controlled rolling step, the ingot is rolled in a recrystallization zone at 1050-1120° C. and in a non-recrystallization zone at 880-950° C., and after rolling, it is rapidly cooled to 400-500° C. and air-cooled.

[0065] In some embodiments, in the controlled rolling step, the reduction amount per rolling pass is 20-30%, and the cumulative reduction rate is 50%.

[0066] The rolling temperature in the recrystallization zone is 1050-1120°C, the rolling reduction per pass is 20-30%, and the cumulative reduction rate is 50%. The recrystallization amount of the deformed austenite is controlled to achieve complete recrystallization as much as possible, refine the austenite grains, and make the structure uniform.

[0067] In some embodiments, in the tempering step, the tempering temperature is 190-360°C.

[0068] In the present application, the tempering temperature is controlled to be 190-360° C. in order to eliminate the structural stress generated during the phase change process. Preferably, the tempering time is 20 min-1 h.

[0069] Example

[0070] The following examples more specifically describe the disclosure of the present application, which are intended for illustrative purposes only, as it will be apparent to those skilled in the art that various modifications and variations are possible within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0071] Example 1

[0072] The invention provides a high-strength and plastic rare earth treated multiphase structure wear-resistant steel plate, whose chemical composition and mass percentage are as follows: C: 0.22wt%, Si: 1.0wt%, Mn: 2.9wt%, Mo: 0.20wt%, Nb: 0.02wt%, Ti: 0.02wt%, Al: 0.035wt%, Ce: 0.03wt%, P: 0.0042wt%, S: 0.0038wt%, B: 0.0011wt%, O: 0.0019wt%, N: 0.0020wt%, Ce: 0-0.04wt%, and the balance is Fe.

[0073] The specific production process is as follows:

[0074] The test steel was smelted, RH, LF-VD treated, and the molten steel was cast into ingots, which were then heated to 1180°C to homogenize the structure. The holding time was calculated as 1min / mm. The recrystallization zone was rolled at a temperature of 1100°C, with a rolling reduction of 20-30% per pass and a cumulative reduction rate of 50%. The amount of recrystallization of the deformed austenite was controlled to achieve complete recrystallization as much as possible, refine the austenite grains, and homogenize the structure. The non-recrystallization zone was rolled with a final rolling temperature of 900°C. After 5-7 rolling passes, a hot-rolled plate with a thickness of 4-12mm was obtained, ensuring that the total reduction rate in the non-recrystallization zone was greater than 45%. After rolling, the steel was cooled to 400-500°C and then air-cooled. The test steel was tempered at 200°C for 30 minutes.

[0075] Example 2

[0076] The present invention provides a high-strength and plastic rare earth treated multiphase structure wear-resistant steel plate, whose chemical composition and mass percentage are as follows: C: 0.18wt%, Si: 1.30wt%, Mn: 3.40wt%, Mo: 0.20wt%, Ti: 0.02wt%, Al: 0.030wt%, Ce: 0.035wt%, P: 0.0056wt%, S: 0.0042wt%, B: 0.0010wt%, O: 0.0018wt%, N: 0.0019wt%, and the balance is Fe.

[0077] The specific production process is as follows:

[0078] The experimental steel was smelted, RH and LF-VD treated, and the molten steel was cast into ingots, which were then heated to 1180°C to homogenize the structure. The holding time was calculated as 1 min / mm.

[0079] Rolling in the recrystallization zone is carried out at a temperature of 1120°C, with a reduction of 20-30% per rolling pass and a cumulative reduction of 50%. The amount of recrystallization of the deformed austenite is controlled to achieve complete recrystallization as much as possible, refine the austenite grains, and make the structure uniform.

[0080] The non-recrystallization zone is rolled, and the final rolling temperature is 910℃. After 5-7 rolling passes, a hot-rolled plate with a thickness of 4-12mm is obtained, and the total reduction rate in the non-recrystallization zone is guaranteed to be greater than 45%. After rolling, the steel is cooled to 400-500℃ and then air-cooled. The test steel is tempered at 200℃ for 30 minutes.

[0081] Example 3

[0082] The present invention provides a high-strength and plastic rare earth treated multiphase structure wear-resistant steel plate, whose chemical composition and mass percentage are as follows: C: 0.22wt%, Si: 1.2wt%, Mn: 2.9wt%, Mo: 0.25wt%, Nb: 0.01wt%, Ti: 0.01wt%, Al: 0.032wt%, Ce: 0.025wt%, B: 0.0011wt%, P: 0.0035wt%, S: 0.0035wt%, O: 0.0018wt%, N: 0.0017wt%, and the balance is Fe.

[0083] The specific production process is as follows:

[0084] The experimental steel was smelted, RH and LF-VD treated, and the molten steel was cast into ingots, which were then heated to 1180°C to homogenize the structure. The holding time was calculated as 1 min / mm.

[0085] Rolling in the recrystallization zone is carried out at a temperature of 1100°C, with a reduction of 20-30% per rolling pass and a cumulative reduction of 50%. The amount of recrystallization of the deformed austenite is controlled to achieve complete recrystallization as much as possible, refine the austenite grains, and make the structure uniform.

[0086] The non-recrystallization zone is rolled, and the final rolling temperature is 910℃. After 5-7 rolling passes, a hot-rolled plate with a thickness of 4-12mm is obtained, and the total reduction rate in the non-recrystallization zone is guaranteed to be greater than 45%. After rolling, the steel is cooled to 400-500℃ and then air-cooled. The test steel is tempered at 200℃ for 30 minutes.

[0087] Example 4

[0088] The present invention provides a high-strength and plastic rare earth treated multiphase structure wear-resistant steel plate, whose chemical composition and mass percentage are as follows: C: 0.21wt%, Si: 1.4wt%, Mn: 3.3wt%, Mo: 0.25wt%, Ti: 0.03wt%, Al: 0.033wt%, Ce: 0.032wt%, P: 0.0029wt%, S: 0.0028wt%, O: 0.0020wt%, N: 0.0018wt%, and the balance is Fe.

[0089] The specific production process is as follows:

[0090] The experimental steel was smelted, RH and LF-VD treated, and the molten steel was cast into ingots, which were then heated to 1180°C to homogenize the structure. The holding time was calculated as 1 min / mm.

[0091] Rolling in the recrystallization zone is carried out at a temperature of 1120°C, with a reduction of 20-30% per rolling pass and a cumulative reduction of 50%. The amount of recrystallization of the deformed austenite is controlled to achieve complete recrystallization as much as possible, refine the austenite grains, and make the structure uniform.

[0092] The non-recrystallization zone is rolled, and the final rolling temperature is 890℃. After 5-7 rolling passes, a hot-rolled plate with a thickness of 4-12mm is obtained, and the total reduction rate in the non-recrystallization zone is guaranteed to be greater than 45%. After rolling, the steel is cooled to 400-500℃ and then air-cooled. The test steel is tempered at 200℃ for 30 minutes.

[0093] Comparative Example 1

[0094] A steel plate, the production process of which is similar to that of Example 1, except that no Ce element is added.

[0095] Comparative Example 2

[0096] A steel plate, the production process of which is similar to that of Example 1, except that the content of Ce element is 0.08%.

[0097] Comparative Example 3

[0098] The production process is similar to that of Example 1, except that the rolling is performed after heating to 1000°C.

[0099] Comparative Example 4

[0100] The production process is similar to that of Example 1, except that the tempering temperature is 400°C.

[0101] The steel plates of Examples 1-4 were subjected to microstructure analysis and room temperature tensile test for mechanical properties, according to the standard GB / T228.1-2010, and the hardness test was measured according to the method of GB / T231.1-2009. The results are shown in Table 1:

[0102]

[0103]

[0104] As can be seen from Table 1, the high-strength and plastic rare earth treated complex phase wear-resistant steel of Examples 1-4 has a Brinell hardness of 440HB to 480HB, a yield strength of more than 1300MPa, and an elongation of ≥15.0%, and has excellent strength, plasticity, wear resistance and bending properties. Figure 1 This is a microstructure diagram of the high-strength and plastic rare earth treated complex phase wear-resistant steel of Example 1 of the present application after hot rolling and tempering at 200°C; Figure 2 This is the room temperature stress-strain curve of the high-strength and plastic rare earth treated complex phase structure wear-resistant steel of Example 1 of the present application after hot rolling and 200°C tempering, which shows that the combination of the chemical composition ratio and production process provided in the present application can effectively make the obtained high-strength and plastic rare earth treated complex phase structure wear-resistant steel have excellent strength and plasticity, wear resistance and bending performance.

[0105] In comparative example 1, Ce element was not added, resulting in insufficient purification of the molten steel, and inclusions formed by oxygen, sulfur, etc. remained in the steel, deteriorating the plastic toughness. In comparative example 2, the Ce element content was too high, resulting in increased costs. If the formed rare earth composite inclusions could not fully float up, they would remain in the steel, which was not conducive to the plastic toughness. In comparative example 3, the heating temperature was low, resulting in the inability of the original austenite grains to be fully recrystallized and fully refined. In comparative example 4, the tempering temperature was high, resulting in the decomposition of martensite, the reduction of dislocation density, and the reduction of steel strength.

[0106] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A high-strength and plastic rare earth treated multi-phase wear-resistant steel, characterized in that: The invention comprises the following components in percentage by mass: C: 0.10-0.30 wt%; Si: 1.0-1.5 wt%; Mn: 2.9-3.5 wt%; Mo: 0.10-0.50 wt%; Nb: 0.01-0.05 wt%; Ti: 0.01-0.10 wt%; Al: 0.030-0.070 wt%; Ce: 0.01-0.05 wt%; P≤0.008 wt%; S≤0.005wt%; B:0.0010~0.0050wt%; O≤0.0020%; N≤0.0020%, the balance is Fe; The metallographic structure of the high-strength and plastic rare earth treated complex phase wear-resistant steel includes 50% to 70% martensite, 26% to 46% bainite, 2% to 10% residual austenite and 0.5% to 2.0% nano-precipitated phase; The high-strength plastic rare earth treated complex phase structure wear-resistant steel has a Brinell hardness of 440HB-480HB, a yield strength greater than 1300MPa, and an elongation of ≥15.0%.

2. A method for producing high-strength and plastic rare earth treated multi-phase wear-resistant steel, used to produce the high-strength and plastic rare earth treated multi-phase wear-resistant steel according to claim 1, characterized in that: include: The molten steel is cast to obtain a casting billet, wherein the casting billet includes the following components in percentage by weight: C: 0.10-0.30wt%; Si: 1.0-1.5wt%; Mn: 2.9-3.5wt%; Mo: 0.10-0.50wt%; Nb: 0.01-0.05%; Ti: 0.01-0.10wt%; Al: 0.030-0.070wt%; Ce: 0.01-0.05wt%; P≤0.008wt%; S≤0.005wt%; B:0.0010~0.0050wt%; O≤0.0020%; N≤0.0020%, the balance is Fe; The ingot is heated in a heating furnace, subjected to controlled rolling, directly quenched and tempered online to obtain high-strength and plastic rare earth treated complex phase structure wear-resistant steel; The metallographic structure of the high-strength and plastic rare earth treated complex phase wear-resistant steel includes 50% to 70% martensite, 26% to 46% bainite, 2% to 10% residual austenite and 0.5% to 2.0% nano-precipitated phase; The high-strength plastic rare earth treated complex phase structure wear-resistant steel has a Brinell hardness of 440HB-480HB, a yield strength greater than 1300MPa, and an elongation of ≥15.0%.

3. The production method according to claim 2, characterized in that: In the step of casting molten steel to obtain a cast ingot, the casting temperature is 1500°C to 1530°C.

4. The production method according to claim 2, characterized in that: In the heating step, the ingot is placed in a heating furnace for homogenization at a heating temperature of 1150-1200°C.

5. The production method according to claim 2, characterized in that: In the controlled rolling step, the ingot is rolled in a recrystallization zone at 1050-1120° C. and in a non-recrystallization zone at 880-950° C., and after rolling, it is rapidly cooled to 400-500° C. and air-cooled.

6. The production method according to claim 5, characterized in that In the controlled rolling step, the reduction in each rolling pass is 20-30%, and the cumulative reduction rate is 50%.

7. The production method according to claim 2, characterized in that: In the tempering step, the tempering temperature is 190-360°C.

Citation Information

Patent Citations

  • A low-alloy, high-toughness QPT wear-resistant steel plate and its preparation method

    CN108004469B

  • Low-alloy high-toughness wear resistant steel plate and manufacturing method thereof

    CN103146997A

  • High-strength high-toughness low-alloy wear-resistant steel and manufacturing method thereof

    CN108950432A

Cited By

  • Steel plate for 1200MPa-grade marine environment anti-fatigue ore conveying pipeline and production method of steel plate

    CN120796863A

  • A 1200mpa grade marine environment fatigue-resistant steel plate for conveying mineral pipelines and a production method thereof

    CN120796863B

  • Rare earth element treatment wear-resistant steel and preparation method thereof

    CN122303726A

  • Rare earth modified wear-resistant steel and method for manufacturing the same

    CN122303726B